Environmental exposure to metals and the development of tauopathies, synucleinopathies, and TDP-43 proteinopathies: A systematic evidence map protocol. (November 2022) - Hester, Kirstin; Kirrane, Ellen; Anderson, Timothy; Kulikowski, Nichole; Simmons, Jane Ellen; Lehmann, David M.
Abstract: Background: Neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and amyotrophic lateral sclerosis are incurable and expected to increase in prevalence in the upcoming decades. Environmental exposure to metals has been suggested as a contributing factor to the development of neurodegenerative disease. This systematic evidence map will identify and characterize the epidemiological and experimental data available on the intersection of eighteen metals of environmental concern (i.e., aluminum, antimony, arsenic, barium, beryllium, cadmium, chromium, cobalt, copper, lead, manganese, mercury, nickel, palladium, radium, silver, vanadium, and zinc) and three neurodegenerative disease clusters (i.e., tauopathies, synucleinopathies, and TDP-43 proteinopathies). We aim to describe the type and amount of evidence available (or lack thereof) for each metal and neurodegenerative disease combination and highlight important knowledge gaps and knowledge clusters for future research. Methods: We will conduct a thorough search using two databases (MEDLINE and Web of Science Core Collection) and grey literature resources. Pre-defined criteria have been developed to identify studies which evaluate at least one of the selected metals and neurodegenerative disease-relevant outcomes (e.g., neuropathology, cognitive function, motor function, disease mortality). At each phase of review, studies will be evaluated by two reviewers. Studies determined to be relevant will be extracted for population, exposure, and outcome information. We will conduct a narrative review of the included studies, and the extracted data will be available in a database hosted on Tableau Public. Conclusion: This protocol documents the decisions made a priori to data collection regarding these objectives.